Investigating awareness and implementation of adrenaline auto-injectors (AAI) via the 'Spare Pens in Schools' scheme in Wales: a cross-sectional pilot study - David Tuthill; Elizabeth Miles; Eliana Panayiotou; Athanasios Hassoulas; Judith Holloway (BMJ Publishing Group, 2024)
Objective To investigate awareness and implementation of the Spare Pens (ie, adrenaline auto-injectors (AAIs)) scheme in primary and secondary schools in two regions in Wales.Design A cross-sectional pilot study employing a mixed research methods approach was carried out.Setting and participants State primary and secondary schools within Swansea and Pembrokeshire regional authorities were invited to take part. For geographical context, Swansea is the second largest city in Wales and is situated in the southwest of the country. Pembrokeshire is located in West Wales, with a large rural population outside of its main towns.Main outcome measures Awareness and implementation of the Spare Pens in Schools scheme. Additionally, compliance with national guidance was measured by administering a questionnaire capturing data on registers, procedures, storage and training in the use of AAIs.Results 35 schools (30 primary, 5 secondary) participated, with 11% and 6% reporting awareness and implementation of the scheme, respectively. No significant differences in awareness or implementation of the scheme were revealed for school type or region. Secondary schools reportedly stored more AAI devices compared with primary schools. The location of stored AAIs varied by school type, with 46.7% of primary schools storing AAIs in the classroom while 80% of secondary schools stored AAIs in the school office. Procedures for accessing AAI training differed, with 83% of primary schools receiving training by school nurses and 60% of secondary schools accessing training via an allergy team.Conclusions The overall poor awareness of the Spare Pens in Schools scheme has resulted in a worrying lack of implementation of generic AAI devices. An urgent review of information dissemination regarding the scheme is required.